The human lung microbiome—A hidden link between microbes and human health and diseases. Issue 3 (16th June 2022) - Yi, Xinzhu; Gao, Jingyuan; Wang, Zhang
Abstract: Once thought to be sterile, the human lung is now well recognized to harbor a consortium of microorganisms collectively known as the lung microbiome. The lung microbiome is altered in an array of lung diseases, including chronic lung diseases such as chronic obstructive pulmonary disease, asthma, and bronchiectasis, acute lung diseases caused by pneumonia, sepsis, and COVID‐19, and other lung complications such as those related to lung transplantation, lung cancer, and human immunodeficiency virus. The effects of lung microbiome in modulating host immunity and inflammation in the lung and distal organs are being elucidated. However, the precise mechanism by which members of microbiota produce structural ligands that interact with host genes and pathways remains largely uncharacterized. Multiple unique challenges, both technically and biologically, exist in the field of lung microbiome, necessitating the development of tailored experimental and analytical approaches to overcome the bottlenecks. In this review, we first provide an overview of the principles and methodologies in studying the lung microbiome. We next review current knowledge of the roles of lung microbiome in human diseases, highlighting mechanistic insights. We finally discuss critical challenges in the field and share our thoughts on broad topics for future investigation. Highlights: Sputum, bronchoalveolar lavage, bronchial brushing, and lung tissue are the routine sample types for the lung microbiome. Multiomics have been increasingly applied for characterizing the lung microbiome. Lung microbiome is broadly implicated in chronic and acute lung diseases, lung cancer, and other lung diseases, with potential mechanistic implications. Current challenges of the lung microbiome studies include low microbial‐to‐host ratio, high disease heterogeneity, and the difficulty in precisely manipulating and culturing the lung microbiome. Future potential topics for lung microbiome studies include understanding the diagnostic potential of the lung microbiome, its spatial dynamics, its mechanistic interaction with the host, and the crosstalk between the lung and distal organs. Abstract : Broad topics of the human lung microbiome are reviewed, including its principles and methodologies, applications to human diseases, mechanistic insights, current challenges, and future potential research avenues.